Analisis kesulitan pemecahan masalah soal cerita materi pecahan ditinjau dari gender studi kasus peserta didik sekolah dasar - Parahita, Nindya Ashiefa; Riyadi, Riyadi; Sriyanto, M. Ismail (Universitas Sebelas Maret, 2022)
This study aims to explain the forms of difficulties experienced by students in solving story problems in fractional material and their causal factors in terms of gender. The indicator of the problem solving steps used is the Polya step. The research subjects were fourth grade students at SD Negeri 1 Tanggeran for the 2021/2022 academic year. This study uses a qualitative method with a case study approach. The data sources in this study were fourth grade students of SD Negeri 1 Tanggeran. The research subjects were two male students and two female students. The data collection techniques used were interviews and document studies. The validity test technique used is time triangulation and technical triangulation. The data analysis technique used is the Miles and Huberman model analysis technique. The results of this study indicate (1) The forms of difficulties experienced by male students are difficulties in planning problem solving and difficulties in solving problems according to plan. (2) The forms of difficulties experienced by female students are difficulties in planning problem solving and difficulties in solving problems according to plan. (3) Factors causing difficulties experienced by male and female students.Keywords: Difficulty, Problem Solving, Gender, Elementary School.